2019
DOI: 10.1589/jpts.31.743
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and types of recurrent stroke: a Saudi hospital based study

Abstract: [Purpose] To identify the risk factors and the stroke types in recurrent stroke patients of Madinah Al-Munawarah city. [Participants and Methods] A prospective research hospital based study was conducted through the year of 2014. The patients were entered in the study when they had recurrent cerebrovascular accident led to hospital admission. All details of patients were obtained include history, demographic data, risk factors and stroke types. [Results] Ninety-four (83.9%) ischaemic strokes, 12 (10.7%) interc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
2
9
1
2
Order By: Relevance
“…Hypertension was identified as a risk factor of stroke recurrence. Our study had found a high frequency of hypertension among recurrent stroke patients (91%), in line with the study of El-Gohary (90.2%) [ 21 ] and Yalcin (89%) [ 26 ], Kocaman (88%) [ 27 ], Morsy (100%) [ 28 ] and Cámara (80%) [ 29 ] but lower frequency was observed in the study of Leo (75%) [ 22 ] and Stahmeyer (69%) [ 17 ]. Some others authors in Scotland [ 25 ] and Thailand [ 30 ] demonstrated that hypertension was not identified as a risk factor of stroke recurrence.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Hypertension was identified as a risk factor of stroke recurrence. Our study had found a high frequency of hypertension among recurrent stroke patients (91%), in line with the study of El-Gohary (90.2%) [ 21 ] and Yalcin (89%) [ 26 ], Kocaman (88%) [ 27 ], Morsy (100%) [ 28 ] and Cámara (80%) [ 29 ] but lower frequency was observed in the study of Leo (75%) [ 22 ] and Stahmeyer (69%) [ 17 ]. Some others authors in Scotland [ 25 ] and Thailand [ 30 ] demonstrated that hypertension was not identified as a risk factor of stroke recurrence.…”
Section: Discussionsupporting
confidence: 92%
“…The mean age of the patients with recurrent stroke was 66.5 ± 11.49 years was similar than in studies from Cameron (62 years) [ 11 ] and Saudi Arabia (67.70 ± 2 years) [ 21 ] but lower than in a study from Suisse, a western country (77 years) [ 22 ]. Stroke occurred in young age in Africa than in Europe due to the long expectancy in Western countries.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…31 Yapılan bir çalışmada, DM'nin %62,5 ile HT'den sonra 2. en sık görülen risk faktörü olduğunu belirtmişlerdir. 32 Bir diğer çalışmada, DM'yi en sık görülen 3. risk faktörü olarak bulmuşlardır. 24 Çalışmamızda da DM, %46,7 oran ile 3. en sık görülen risk faktörü olarak bulunmuştur.…”
Section: Discussionunclassified
“…Recurrent strokes are dangerous threats and can be fatal; thus, we should avoid them. Prevention of recurrent strokes is a valuable process, and data need to be available to support efforts to minimize the incident that can avert high treatment and rehabilitation costs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%